2004
DOI: 10.1161/01.hyp.0000125698.00128.64
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Drug Pharmacokinetics for Phenotyping Individual Renin Response to Angiotensin II Blockade in Humans

Abstract: Abstract-Renin release into plasma has been used to investigate the drug dose-dependence of renin-angiotensin system inhibition because it is proportional to the interruption of the permanent negative feedback loop of angiotensin II on renin secretion. We investigated the 24-hour between-subject differences in renin profiles by analyzing the time-dependence of individual renin responses in 16 mildly sodium-depleted normotensive subjects exposed in a 4-period crossover study to single oral doses of 8-and 16-mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
4
23
0
1
Order By: Relevance
“…The RPI is a pharmacokinetic/pharmacodynamic index that takes into account actual drug exposure rather than the oral dose of the drug administered and has been used previously to characterize two different AT1R antagonists, valsartan and candesartan (20). This correction is especially important in studies in which drug pharmacokinetics are nonlinear, as was the case in the present study.…”
Section: Comparison Of the Hormonal Effects Of The Renin Inhibitor Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPI is a pharmacokinetic/pharmacodynamic index that takes into account actual drug exposure rather than the oral dose of the drug administered and has been used previously to characterize two different AT1R antagonists, valsartan and candesartan (20). This correction is especially important in studies in which drug pharmacokinetics are nonlinear, as was the case in the present study.…”
Section: Comparison Of the Hormonal Effects Of The Renin Inhibitor Anmentioning
confidence: 99%
“…This analysis defines for each individual a normalized index of active renin release or "renin/pharmacokinetic index" (RPI), expressed in pg active renin/ml per ng drug/ml (20). The RPI calculated for A300 was 7.87 pg/ml per ng/ml (95% CI, 6.21 to 9.97), and the RPI calculated for V160 was 0.34 pg/ml per ng/ml (95% CI, 0.21 to 0.55).…”
Section: Pharmacokinetic/pharmacodynamic Interactions That Affect Plamentioning
confidence: 99%
“…1,2 Whether they also increase kidney renin is still being debated. [1][2][3] The rise in blood plasma has been suggested to be larger than during other types of RAS blockade, 4 either because the degree of RAS blockade is superior during renin inhibition 5 and/or because renin inhibitors increase the half-life of renin. 6 It may also be an artifact, because renin inhibitors "activate" the precursor of renin, prorenin ( Figure 1).…”
mentioning
confidence: 99%
“…The availability of oral valsartan, a readily active carboxylic acid derivative, 22 was not significantly affected by dietary sodium intake, even though the 2 diets could not be considered bioequivalent because of the high within-subject variability of valsartan pharmacokinetics, consistent with previous findings. 10 Ramipril was the only drug for which bioequivalence was strictly achieved between the 2 diets. It is a monoester carboxylic prodrug with a bioavailability of 50% to 60% extensively and rapidly metabolized to its active diacid derivative, ramiprilat, mainly in the liver.…”
Section: Pharmacokinetic Consequences Of Differences In Dietary Sodiumentioning
confidence: 99%
“…9 Thus, any change in urinary excretion of atenolol with the sodium content of the diet should directly reflect a change in the net intestinal absorption of the drug in healthy subjects with normal renal function. The pharmacodynamic consequences of dietary sodium-induced changes in the pharmacokinetics of these drugs were assessed by determining the druginduced increase in plasma renin concentration (PRC) for the angiotensin-converting enzyme inhibitor and the angiotensin II receptor blockers resulting from interruption of the angiotensin II negative feedback loop on renin release 10 ; and the drug-induced changes in PR interval duration and heart rate (HR) on ECG recordings for atenolol. 6 We found that sodium status modulated the pharmacokinetics of candesartan and atenolol, with measurable but mild effects on the selected pharmacodynamic end points.…”
mentioning
confidence: 99%